BS EN IEC 60331-4. Tests for electric cables under fire conditions. Circuit integrity. Part 4. Test method for fire with shock at a temperature of at least 830 °C for cables of rated voltage higher than 1kV up to and including 30 kV (13th November 2020) - British Standards Institution,
No abstract available